2020
DOI: 10.3390/brainsci10020084
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Siamese Convolution Neural Network for Multi-Class Classification of Alzheimer Disease

Abstract: Alzheimer’s disease (AD) may cause damage to the memory cells permanently, which results in the form of dementia. The diagnosis of Alzheimer’s disease at an early stage is a problematic task for researchers. For this, machine learning and deep convolutional neural network (CNN) based approaches are readily available to solve various problems related to brain image data analysis. In clinical research, magnetic resonance imaging (MRI) is used to diagnose AD. For accurate classification of dementia stages, we nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(80 citation statements)
references
References 48 publications
1
79
0
Order By: Relevance
“…The multiclass classification includes the classification among the HC, ALS, PD and HD at the same time. Even though the application of the CNN in the multiclass classification has been used in different domains of medical research such as in [43][44][45][46][47], the multiclass classification is the novelty of this study and existing literature did not do the multiclass classification.…”
Section: Resultsmentioning
confidence: 99%
“…The multiclass classification includes the classification among the HC, ALS, PD and HD at the same time. Even though the application of the CNN in the multiclass classification has been used in different domains of medical research such as in [43][44][45][46][47], the multiclass classification is the novelty of this study and existing literature did not do the multiclass classification.…”
Section: Resultsmentioning
confidence: 99%
“…The recent development of deep learning methods has drawn much attention for brain image analysis [ 13 , 14 , 15 ]. These methods may provide solutions for predicting molecular subtype gliomas by automatic feature learning.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various optimization algorithms reported here for the proper selection of features, it was revealed that Grey Wolf Optimization showed promising results. Motivated by Oxford Net, the Siamese CNN model was studied in [104] for multi-class classification of AD. The superiority of the proposed model as compared to the state-of-the art models was authenticated by obtaining an excellent classification accuracy of 99.05%.…”
Section: ) Dl-based Approaches In Ad Diagnosismentioning
confidence: 99%